2014
DOI: 10.1080/07391102.2014.929535
|View full text |Cite
|
Sign up to set email alerts
|

Shape-based virtual screening, docking, and molecular dynamics simulations to identifyMtb-ASADH inhibitors

Abstract: Aspartate β-semialdehyde dehydrogenase (ASADH) is a key enzyme for the biosynthesis of essential amino acids and several important metabolites in microbes. Inhibition of ASADH enzyme is a promising drug target strategy against Mycobacterium tuberculosis (Mtb). In this work, in silico approach was used to identify potent inhibitors of Mtb-ASADH. Aspartyl β-difluorophosphonate (β-AFP), a known lead compound, was used to understand the molecular recognition interactions (using molecular docking and molecular dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…However, more models should be constructed to cover more diverse chemical space if different shapes are available (Perez-Nueno and Ritchie, 2011 ), particularly for highly flexible proteins. Some studies using the shape-focused method have been reported in recent years (Reddy et al, 2013 ; Chen et al, 2015 ; Kumar et al, 2015 ; Prabhu and Singh, 2019 ). For example, Chen et al ( 2015 ) presented a shape-based virtual screening to find new cores for the design of acetylcholinesterase (AChE) inhibitors.…”
Section: In Silico Approachesmentioning
confidence: 99%
“…However, more models should be constructed to cover more diverse chemical space if different shapes are available (Perez-Nueno and Ritchie, 2011 ), particularly for highly flexible proteins. Some studies using the shape-focused method have been reported in recent years (Reddy et al, 2013 ; Chen et al, 2015 ; Kumar et al, 2015 ; Prabhu and Singh, 2019 ). For example, Chen et al ( 2015 ) presented a shape-based virtual screening to find new cores for the design of acetylcholinesterase (AChE) inhibitors.…”
Section: In Silico Approachesmentioning
confidence: 99%
“…The Cox's group was particularly active in the design of phosphonic aspartic derivatives including phosphoramidates, phosphonates (see 2.5), monofluorophosphonates (see 3.1.3), and difluorophosphonates [160] . Aspartyl β‐difluorophosphonate (β‐AFP) of 218 , was identified as a lead compound and used to understand the molecular recognition interactions with ASA‐DH [161–162] . The synthesis of 218 was reported via different routes that all exploited aspartic acid as starting chiral substrate.…”
Section: Asymmetric Construction Of Amino Acid Fluorophosphonate Derimentioning
confidence: 99%
“…This was carried out using Phase shape screening application from the Schrodinger suite [ 10 ]. This technique employs the methodology of screening of database based on shape and electrostatic properties of the known molecule to retract similar type of molecules from natural molecule database [ 11 ]. The screened molecules were predicted to show similar kind of binding modes with active site residues and in turn may produce similar type of activity.…”
Section: Methodsmentioning
confidence: 99%